Muscle function of painful versus non-painful swimmer's shoulder
A comparison of swimmers with painful and non-painful shoulders was made. The painful group's force production was mainly attributed to the internal rotator muscles (anterior deltoid, pectoralis major, and latissimus dorsi). The external rotator muscles (infraspinatus, teres minor, and supraspinatus) function to stabilize and maintain the integrity of the shoulder joint. Their activity was lower in the painful than the non-painful group. The muscular activity of the internal and external rotators was balanced in the non-painful group. The painful group's biomechanical efficiency was at least 13% less than the non-painful group at all speeds, that is, their technique was worse. The study suggests that the strong internal rotators were pulling the shoulder slightly out of joint which resulted in excessive irritation and eventual pain in the rotator cuff. Implications: There are several implications from this study which may lead to prevention of occurrences of swimmer's shoulder. - Strengthen the external rotator muscles to balance the pulling muscles associated with internal rotation. That extra strength should be used to maintain the integrity of the joint. - Increase body roll so that the line of the shoulders is more in line with the upper arm in the middle of the pull. In that position, the shoulder joint will be loaded equally by the mechanical forces generated along that line. - If the body roll is already in the vicinity of 30 to 40 degrees, emphasize a pulling action with the elbow wide and a greater elbow bend in the most productive phase of the pull. - At the first sign of pain, institute correct external rotator strength training and concentrate on greater body roll as an item of technique "revision."